2020
DOI: 10.1038/s41379-019-0332-7
|View full text |Cite
|
Sign up to set email alerts
|

Chrysotile fibers in tissue adjacent to laryngeal squamous cell carcinoma in cases with a history of occupational asbestos exposure

Abstract: Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In our subgroup analysis of asbestos species, we found that exposure to chrysolite and mixed asbestos (containing chrysolite) was significantly associated with an increased SMR in esophageal cancer. A similar result was found in Wronkiewicz et al’s study, which showed tissue surrounding pharyngeal cancer and laryngeal cancer in 6 cases with a history of occupational asbestos exposure through scanning electron microscopy, and chrysolite fibers were noted in the tissues of 3 cases [ 58 ]. Our results did not show a significantly increased SMR in participants who were exposed to amosite and crocidolite.…”
Section: Discussionsupporting
confidence: 83%
“…In our subgroup analysis of asbestos species, we found that exposure to chrysolite and mixed asbestos (containing chrysolite) was significantly associated with an increased SMR in esophageal cancer. A similar result was found in Wronkiewicz et al’s study, which showed tissue surrounding pharyngeal cancer and laryngeal cancer in 6 cases with a history of occupational asbestos exposure through scanning electron microscopy, and chrysolite fibers were noted in the tissues of 3 cases [ 58 ]. Our results did not show a significantly increased SMR in participants who were exposed to amosite and crocidolite.…”
Section: Discussionsupporting
confidence: 83%
“…The main risk factors for LC are tobacco and alcohol use, which would contribute to about 90% of the overall worldwide mortality for LC [16]. Exposure to textile dust [17], polyaromatic hydrocarbons, and asbestos [18], infection with human papillomavirus [19], and red meat consumption [20] also contribute to the elevated incidence of LC. Clearly, control of exposure to risk factors and adoption of healthy lifestyles, maintaining a healthy weight should be strengthened to reduce the global burden of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Firefighters are exposed to a wide variety of known carcinogenic chemicals and particulates,3 6 including asbestos, which has been associated with pharyngeal and laryngeal cancer22–24 29—including detection of chrysotile fibres adjacent to a laryngeal tumour in a case with an occupational history as a firefighter33—and PAH 21 22…”
Section: Discussionmentioning
confidence: 99%